2018
DOI: 10.1071/is18024
|View full text |Cite
|
Sign up to set email alerts
|

Cryptic speciation in a biodiversity hotspot: multilocus molecular data reveal new velvet worm species from Western Australia (Onychophora : Peripatopsidae : Kumbadjena)

Abstract: There is a yet uncovered multitude of species to be found among Western Australian Onychophora. Kumbadjena, one of the two genera that reside in this region, has been previously suggested to house an extensive species complex. Morphology alone has not been able to elucidate the diversity in this genus and has instead muddled species delineations. Topologies and species delimitation analyses resulting from the sequences of two mitochondrial ribosomal markers (12S rRNA and 16S rRNA), one nuclear ribosomal marker… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 63 publications
0
12
0
Order By: Relevance
“…It is important to point out that Macroperipatus and Epiperipatus are problematic genera (Oliveira & Wieloch, 2005, Oliveira et al, 2010, 2012a: considering the general onychophoran biology, they exhibit an unlikely broad distribution (Oliveira et al, 2011;Daniels et al, 2016;Cunha et al, 2017;Sato et al, 2018;Barnes & Daniels, 2019), which causes an overlap in characters with those of other genera. This is especially true in Epiperipatus (Sampaio-Costa et al, 2018), as its diagnostic characters are present in most species.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It is important to point out that Macroperipatus and Epiperipatus are problematic genera (Oliveira & Wieloch, 2005, Oliveira et al, 2010, 2012a: considering the general onychophoran biology, they exhibit an unlikely broad distribution (Oliveira et al, 2011;Daniels et al, 2016;Cunha et al, 2017;Sato et al, 2018;Barnes & Daniels, 2019), which causes an overlap in characters with those of other genera. This is especially true in Epiperipatus (Sampaio-Costa et al, 2018), as its diagnostic characters are present in most species.…”
Section: Discussionmentioning
confidence: 99%
“…Except for the pioneer works of Trewick (1998Trewick ( , 1999Trewick ( , 2000, none other onychophoran's taxonomist has recognized that molecular genetics is the best tool available to identify taxa within this phylum (see Gleeson & Ruhberg, 2010). Particularly, for cryptic species, this is possibly the only way (Briscoe, & Tait, 1995;Daniels et al, 2016;Cunha et al, 2017;Sato et al, 2018). Certainly, morphology and biogeography should be used as auxiliary tools.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent evolutionary work on velvet worms has focused on aspects of continental-scale biogeography and systematics (Allwood et al, 2010;Costa et al, 2021;Giribet et al, 2018;Murienne et al, 2014;Oliveira et al, 2013Oliveira et al, , 2016 and in understanding smallscale biogeographic patterns in relation to cryptic speciation, by a combination of phylogenetic and population genetics (e.g. Barnes & Daniels, 2019;Daniels et al, 2009Daniels et al, , 2016Daniels & Ruhberg, 2010;Oliveira et al, 2011Oliveira et al, , 2018Sato et al, 2018). Phylogenetic research has shown a main difference between the two families of Onychophora.…”
Section: Introductionmentioning
confidence: 99%